TRANSFUSIONAL SUPPORT IN HSCT - Kondo, Andrea Tiemi; Prata, Karen Lima; Souza, Aline Miranda de; Lira, Sanny Marcele da Costa; Ribeiro, Andreza Alice Feitosa (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2021)
THE BRAZILIAN SOCIETY FOR BLOOD AND MARROW TRANSPLANTATION (SBTMO) PRESENTS THE BRAZILIAN GUIDELINES ON HEMATOPOIETIC STEM CELL TRANSPLANTATION